Computational modeling and experimental verification of cathode catalyst layer on PEM fuel cells - Kil, Seyma; Ozdemir, Oguz Kaan; Insel, Mert Akin; Sadikoglu, Hasan (PERGAMON-ELSEVIER SCIENCE LTD, 2022)
Fuel cell systems are environmentally friendly energy converters that directly transform the chemical energy of the fuel to electricity. The proton exchange membrane (PEM) fuel cells are one of the most common type of fuel cells since they deliver high power density and are lighter and smaller when compared to the other cells. However, commercialization of the PEM fuel cells is challenging due to the high cost of its components. In addition to high catalyst costs, the problem of poor water management is also a vital issue that needs to be overcome. While the gas diffusion layer of a fuel cell is essential for removing the by-product water, the Nafion solution contained in the catalyst layer has hydrophobic prop-erties and is crucial for both preventing the water accumulation and increasing the effec-tiveness of the fuel cell. In this study, the effects of Carbon:Nafion ratio on the reduction potential was investigated. The cyclic voltammograms (CV) was produced for each ratio, and it was shown that the CVs exhibit characteristics of hydrogen adsorption/desorption peaks. All the linear sweep voltammogram (LSV) curves revealed well distinguished regions of kinetic, mixed and diffusion limited reaction rate. As a result, it was observed that the ratio of 1:5 resulted higher reduction potential compared to 1:3 and 1:7. Finally, a mathe-matical model was purposed, in which related the rotation rate and platinum coating with the current density, in order to gain insight about the responses of the fuel cell system. The constructed model is tested and validated experimentally for various parameters that are present in the system, and it may be utilized to determine oxygen reaction activities of the catalysts without performing any unnecessary electrochemical tests.(c) 2022 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Catalyst layer; Hydrophobic layer; Mathematical model; Oxygen reduction reaction; Proton exchange membrane fuel cell; Pt electrocatalyst; GAS-DIFFUSION LAYERS; TRANSPORT PHENOMENA; PERFORMANCE; DEGRADATION; TEMPERATURE; THICKNESS; SYSTEM; OPTIMIZATION; DURABILITY; MANAGEMENT; Chemistry; Electrochemistry; Energy & Fuels